Economic Resilience Through the Empowerment of Impoverished Female Household Heads in Jombang Regency - Alifiulathin Utaminingsih; Qurnia Indah Permata Sari; Nur Himmatul Fitriyah (Wacana: Jurnal Sosial dan Humaniora)
This research aims to understand how the economic resilience of impoverished female household heads in Jombang Regency can be improved through empowerment programs and to identify strategies that support the implementation of the Female Household Head Empowerment Program (PEKKA). This topic was chosen because female household heads often face severe economic challenges and require specialized support to enhance their well-being. The research method employed is a case study on impoverished female household heads in Jombang Regency, with data collected through in-depth interviews, observations, and analysis of relevant documents. The results indicate that the economic resilience of impoverished female household heads in Jombang Regency has improved through various empowerment programs conducted by PEKKA, supported by the Jombang Regency Office of Population Control and Family Planning, Women's Empowerment, and Child Protection (DP2KBP3A), as well as the Jombang Women's Crisis Center (WCC). These empowerment programs include skill training, social and psychological support, inter-agency collaboration, market access facilitation, business legalization, network and communication strengthening, recognition and appreciation, financial aid, and credit access. This study provides important insights into how empowerment strategies can effectively enhance impoverished female household heads' economic resilience and well-being. The conclusion of this research underscores the necessity of an integrated approach and sustained support for the success of such empowerment programs. Recommendations are provided to strengthen similar policies and programs in other regions.